Pre-test habituation improves the reliability of a handheld test of mechanical nociceptive threshold in dairy cows. (October 2015) - Raundal, P.M.; Andersen, P.H.; Toft, N.; Herskin, M.S.; Forkman, B.; Munksgaard, L.; de Passillé, A.M.; Rushen, J.
Abstract: Mechanical nociceptive threshold (MNT) testing has been used to investigate aspects of painful states in bovine claws. We investigated a handheld tool, where the applied stimulation force was monitored continuously relative to a pre-encoded based target force. The effect on MNT of two pre-testing habituation procedures was performed in two different experiments comprising a total of 88 sound Holsteins dairy cows kept either inside or outside their home environment. MNT testing was performed using five consecutive mechanical nociceptive stimulations per cow per test at a fixed pre-encoded target rate of 2.1 N/s. The habituation procedure performed in dairy cows kept in their home environment led to lowered intra-individual coefficient of variation of MNT ( P < 0.001), increased MNT ( P < 0.001) and decreased the discrepancy between applied and target force during stimulations ( P < 0.001). Pre-test habituation improved the reliability of the handheld tool when used in dairy cows kept in their home environment. Highlights: Mechanical nociceptive threshold testing in dairy cows by a handheld tool. Habituation to the test procedure increased the reliability of MNT testing. Habituation decreased discrepancy between applied and target force during stimulations.